PKM PENERAPAN PLTS PADA KAWASAN PERTANIAN HIDROGANIK PADI DI BENGKEL MIMPI KABUPATEN MALANG - Budiyanto, Hery; Setiawan, Aries Boedi; Siswati, Aris (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2021)
Currently, rice farming land is getting narrower because it is pressed for housing. Ways are needed to utilize narrow land to develop a rice farming system, including hydrogenic farming, which is an organic cultivation system by planting rice on humus soil in plastic cups planted in a row of paralon pipes above fish ponds, integrating a hydro system (water circulation) nutritious and organic systems (without chemical fertilizers). This Community Partnership Program aims to deal with the problems experienced by service partners, namely the Self-help Agricultural and Rural Training Center "Bengkel Mimpi" in Malang Regency which carries out hydroganic rice cultivation, namely how to obtain alternative sources of electricity so that financial expenditures for electricity can be increased. So far, only state electricity company can save more/reduce, so that the solution and output target implemented in overcoming these problems is in the form of a solar power plant which is used to drive 12 hydraulic water pumps. The method of service is action research: discussion, design and application of solar power plants. After going through technical calculations, 6 100 wp solar panels were installed, complete with support brackets, 3 100 AH batteries, 1 solar charge controller, 1 3000 WA inverter, 12 water pumps. The advantage of this solar power plant is the design aspect of the solar panel support bracket which is made attractively resembles the shape of a sunflower. The test results have been carried out in sunny conditions this solar power plant produces 2,144 Watt Hours. The output of this Community Partnership Program can be used as a model for alternative sources of electricity in other villages nationally, especially on hydrogenic and hydroponic agricultural lands which are located far from the state electricity network. Keywords: hydrogenic rice, action research, solar power generation